Recent Advances and Implication of Bioengineered Nanomaterials in Cancer Theranostics - Rai, Ayushi (Medicina (Kaunas), 2021)
Cancer is one of the most common causes of death and affects millions of lives every year. In addition to non-infectious carcinogens, infectious agents contribute significantly to increased incidence of several cancers. Several therapeutic techniques have been used for the treatment of such cancers. Recently, nanotechnology has emerged to advance the diagnosis, imaging, and therapeutics of various cancer types. Nanomaterials have multiple advantages over other materials due to their small size and high surface area, which allow retention and controlled drug release to improve the anti-cancer property. Most cancer therapies have been known to damage healthy cells due to poor specificity, which can be avoided by using nanosized particles. Nanomaterials can be combined with various types of biomaterials to make it less toxic and improve its biocompatibility. Based on these properties, several nanomaterials have been developed which possess excellent anti-cancer efficacy potential and improved diagnosis. This review presents the latest update on novel nanomaterials used to improve the diagnostic and therapeutic of pathogen-associated and non-pathogenic cancers. We further highlighted mechanistic insights into their mode of action, improved features, and limitations.